THE INTERNAL MANIFESTATIONS OF NETWORK EFFECTS IN THE PROCESS OF BANKING EXPANSION - Anton A. Moskvichev; Ludmila B. Parfenova (Статистика и экономика)
The article presents the results of the research of modern trendsin network banking expansion of the post-industrial economy. Special attention is paid to the technological factors that havea signiﬁcant impact on interactions of market participants.It`s proposed a new approach in the theory of common rulesof changes in scale economies along with the growth of thenetwork of credit institution. The results of investigation contain conclusions on the favorable impact of network effects upon the growth of the production function. Besides, there is apreservation of sustainable economies of scale effect during the network banking expansion on conditions of the increasingbanking products sales. The study is detected to the correlation between direct and inverse network effects and the managementof internal processes in banking business and communicationwith external partners.